The development of the adoption institution and the identity of a child. Legal consequences and ethical dilemmas - Rakoczy, Tomasz (The Opole Studies in Administration and Law, 2020)
The Polish family law has developed three types of adoption: incomplete, full and total. Each of them is a reply to the arising new threat of the good of the child. Simultaneously each of them indeed influences the identity of the child. As a result of the preparation a civil status of the child is changing. The adoption is connected with secrecy. Originally it was firmly stressed. At present the doctrine as well as practitioners think that holding on to secrecy is not necessarily purposeful. The presented legal structures give rise to a series of ethical dilemmas. Firstly, the question arises about supporting biological parents in leaving the child in their family. The law does not regulate such efforts. It only orders “to wait” six weeks for making the decision on adoption by the mother of the child. Secondly, the similar question arises on the part of adopting parents. What motivation do they have? Is this good of the child or their own good alone? Is combining these goods in one act possible? Also the question arises with reference to respecting the religious membership of the child. As a result of the adoption the surname of the child is changed. Even a change of the child’s first name is possible. The religious identity remains unchanged. The practice shows that family relations with the adopted child are not always successful. The rich case law proves that resolving adoption is not always possible.